The landscape of chromothripsis across adult cancer types - Natalia Voronina (Nature Portfolio, 2020)
The shattering of chromosomes is a dramatic early event in tumourigenesis and is termed chromothripsis. Here, the authors examine chromothripsis across 28 tumour types and show that 49% of cancers exhibit features of chromothripsis.